Preparation and Antifungal Properties of Cyclopropyl Derivatives of 3-Aminoquinazolin-4(3H)-one and Salicylal Schiff Base Nickel(II) Chelate Complex - Alexander N. Fedotov; Elena V. Trofimova; Victor A. Tafeenko; Igor P. Gloriozov; Andrey V. Mironov; Alexandre N. Zakharov (Inorganics)
N-substituted 2-cyclopropyl-3-R-quinazoline-4()-ones [R: NH2 (1), N=CH(2-hydroxyphenyl) (2)] and Ni(II) chelate compound of 2-cyclopropyl-3-[(Z)-(2-hydroxybenzylidene)amino]quinazoline-4(3H)-one (3) were synthesized and their structures and properties were characterized using X-ray diffraction data, computational optimization, 1H and 13C NMR, IR spectroscopy, and diffuse reflectance spectra. Compounds 1 and 2 are monoclinic (space group P21/n). Unit cell parameters (a, b, c) are 9.2529; 4.7246; 22.3460 Å and 10.2811; 4.6959; 30.972 Å for 1 and 2, respectively. Nickel(II) chelate compound crystallizes in an orthorhombic crystal system (space group Pbca). Unit cell parameters (a, b, c) for 3 are 26.5010; 14.8791; 8.904975 Å, respectively. Schiff base 2 in the crystalline state exhibits two rotary isomers in a molar ratio of 1:3, among which only a minor component as a bidentate ligand can form compound 3 with Ni(II) ion. Nickel(II) ion in 3 is coordinated by N donor atoms and deprotonated O atoms of Schiff base ligands to form square-planar chelate node NiN2O2. All synthesized compounds revealed high antifungal activity against bread mold (Mucor mucedo).